Implementing Think-Pair-Share Strategy and Audio-Visual Media to Overcome Student Sleepiness During English Lessons at SMA Nurul Jadid - Cahyani, Intan; Mohammad Sofyan Adi Pranata; Mustaina (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The purpose of this investigation was to tackle the problem of students feeling sleepy in English class at Nurul Jadid Senior High School by using a Think-Pair-Share (TPS) method along with audio-visual resources. The methodology utilized was Classroom Action Research, carried out across a pair of cycles, with each cycle encompassing planning, acting, observing, and reflecting. Thirty-two students from the eleventh grade took part in the study. The methods for gathering information involved observation forms, scales for rating sleepiness, conversations, and records. The findings demonstrated a noticeable lessening of student drowsiness. Initial information prior to the cycles showed that 59.4% of the students were sleepy, but this fell to 28.1% in the first cycle and then even further to just 9.4% in the second cycle. There was a significant rise in student involvement, with active participation jumping from 34.4% up to 84.4%. Using TPS alongside audio-visual tools is a fresh way to deal with sleepiness in the classroom by bringing together working as a group with stimulation for multiple senses.